Mapeamento e caracterização do meio físico como indicativo de susceptibilidade erosiva na bacia hidrográfica do ribeirão São Lourenço Ituiutaba/MG - Silva, Giliander Allan da (2014)
The research was conducted in the Ribeirão São Lourenço watershed of the Ituiutaba and Prata municipalities. This watershed, in the west of the State of Minas Gerais, covers 295 km². The São Lourenço stream is the principal source of water for the city of Ituiutaba. The local agriculture has been characterized as an important economic activity in the study area but is also the main factor in environmental degradation. In the last four years three new areas have been urbanized in the basin. This activity also, could further impact the hydrological situation of the basin. Thus, the present study aims to characterize the attributes of the physical environment in order to identify susceptibility to the dangers of erosion. Fieldwork, academic research, topographic maps, photo-interpretation of satellite images, aerial photographs and radar operations were used to elaborate the cartographic bases of the study. Field trials with the Guelph permeameter and laboratory data (physical indices, erodibility, aggregate stability, particle size) made it possible to define five classes of unconsolidated materials. Operations with controlled overlapping themes were conducted using ArcMap 9.3 software. Three maps were generated to present the environmental conditions of the basin in relation to the occurrence of erosion: the Runoff Potential (3rd level), Potential Erosion (4th level) and Susceptibility to Erosion (5th level). The latter presents three levels of erosion susceptibility: high, medium and low. Results demonstrate that areas of high susceptibility occupy 9,1% of the basin, with areas of slopes above 10% and the presence of gullies. Locations characterized by average susceptibility occupy 36,9% of the watershed. These areas include medium potential for erosion (map of the 4th level) and the occurrence of ravine type erosion. The areas with low susceptibility to erosion were areas of flat terrain. These areas occupy 54% of the study area and do not present problems of erosion. Together, the areas of high and medium susceptibility to erosion, however, represent almost half of the watershed area. In these locations, erosional features (gullies and/or ravines) are already present. Study results from the area of the São Lourenço basin thus imply the need for appropriate management practices to protect their natural weaknesses. It is hoped that the information generated in this study will contribute to effort on the part of local public agencies in planning policy for the basin and subsequently for the water resources. Furthermore, it is hoped that additional research will develop from this pioneer discussion of the watershed that supplies Ituiutaba (MG).